«…В этом страшном сраме…» Рефлексия репрессий в стихах августа 1968 года о вторжении в Чехословакию - Rosenbljum, Ol'ga (Wiener Slawistischer Almanach, 2024)
The article analyzes the poems of four poets who condemned the invasion of Soviet troops into Czechoslovakia in August 1968 (Alexander Tvardovsky, Evgeny Evtushenko, Alexander Galich, Alexander Timofeevsky). The objective is to describe the ways of reflecting repressions in the USSR and one’s own responsibility for it as they existed at the end of 1968, i.e., 15 years after the first literary responses to the end of the Stalin era had appeared. Two ways of characterizing the zone of responsibility for this invasion are described here: the attribution of responsibility for the repression to the Soviet authorities by representatives of “official literature”, and the problematization of the moral responsibility of each individual citizen of the country by representatives of “unofficial literature”. It is suggested that the characteristic feature of the description of the repressions for both trends was the reference to the classics, and that the representatives of the “unofficial literature” interpreted the repressions in the context of “eternal themes” (such as references to the Bible), thus partially relativizing the degree of criminality of the Soviet state, while the strongest accusations against the official Soviet authorities were voiced by those poets who were accustomed to addressing the mass reader and who, with reference to the classics, chose the themes of “bureaucrats” and the “Little Man”.